Association of Adverse Outcomes in Terms of Mortality in Patients with Cirrhosis Presented with Coronavirus Disease - Hashmatullah Khan, Muhammad Amjad Khan, Muhammad Afzal, Sultan Zeb Khan, Zia Ul Mustafa, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: The global pandemic caused by the novel coronavirus (SARS-CoV-2) has triggered widespread morbidity and mortality, leading to a significant healthcare burden worldwide. Objective: The main objective of the study is to find the association of adverse outcomes in terms of mortality in patients with cirrhosis presented with coronavirus disease. Methodology: This retrospective cohort study was conducted at Lady Reading Hospital, Peshawar during January 2021 to June 2022. Data were collected from 78 patients. Data were collected retrospectively and all information extracted included demographic data (age, gender, underlying health conditions like diabetes and hypertension), clinical characteristics related to cirrhosisand clinical details regarding COVID-19 (severity at the time of admission, need for respiratory support, treatments administered, and length of hospital stay). Results: Data were collected from 78 patients, with a mean age of 55.3 ± 10.2 years. The majority of patients were male (65%) and had alcohol-related liver disease as the primary etiology (43%), followed by viral hepatitis (30%). At the time of admission, 15% of patients had mild COVID-19, 17% had moderate, 40% had severe, and 28% had critical disease. The Child-Pugh classification showed 40% of patients had class A cirrhosis, 35% had class B, and 25% had class C.The need for mechanical ventilation was significantly higher in patients with more severe liver disease, with 42% of patients with Child-Pugh class A cirrhosis requiring ventilation compared to 58% of those with class B cirrhosis and 74% of those with class C cirrhosis. Conclusion: It is concluded that cirrhosis significantly increases the risk of adverse outcomes, including higher mortality, ICU admission, and the need for mechanical ventilation in patients with COVID-19. Advanced liver disease, as indicated by higher Child-Pugh and MELD scores, is associated with worse clinical outcomes. Keywords: Liver Cirrhosis, Coronavirus Disease, Morality